(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2013)
Erectile dysfunction (ED) defined as "the inability to achieve or maintain an erection sufficient for sexual intercourse”—is one of the most common sexual dysfunctions in men. Some men assume that erectile failure is a natural part of the aging process and tolerate it, for others it is devastating. Withdrawal from sexual intimacy because of fear of failure can damage relationships and have a profound effect on overall wellbeing for the couple. Erectile dysfunction often accompanies chronic illnesses, such as diabetes mellitus, heart disease, hypertension, and a variety of neurological diseases. Therefore, physicians need to identify any underlying co-existing organic diseases in their patients presenting with ED. Whenever possible, patients are encouraged to attend their consultation sessions with their partners because ED is a condition affecting the couple’ and not just the man. Psychogenic aspects of ED should also be explored during the consultation. The first-line treatment of ED is oral phosphodiesterase-5 inhibitors. For those who do not respond to oral therapy, there is no defined ’step-ladder’ escalation in alternative therapy. It is up to the physician to discuss the options with the patient or couple and reach a decision based on their preference. JCMCTA 2012 ; 23 (2): 5-17